HEPATITIS "B" VACCINATION: APPLICATIONS AND IMPLICATIONS - Khan, Saleem Afzal; Zaman, Sharif -uz- (Journal of Ayub Medical College Abbottabad, 1989)
In this review article, we have discussed different vaccines, their safety and the high risk groups which should be vaccinated. Two hepatitis "B" vaccines were licensed, the plasma derived MB Vax (Merck Sharp and Dohme Ltd) in 1982 and the recombinant Engerix "B" (Smith-Klinc and French Lab Ltd) in 1987. HB vax, prepared in U.S. has been the most widely used and researched vaccine. There has been over 15 years of experience with safety and over 12 years’ clinical experience. Preparation involves harvesting non-infectious sub-units from the plasma via plasmapheresis from selected chronic HBsAg +ive, HBsAg + ive, healthy carriers, which are then inactivated by triple chemical inactivation. This process inactivates all living organisms previously known to infect man, including HIV agents. Each batch is subjected to 05 weeks of purification and safety-testing. The second type of genetically engineered vaccine "Engerix B" is prepared from human blood with whole virion particles harvested from serum of chronic carriers. There is no evidence that the two types of vaccines differ significantly with respect to safety, side effects, immogenicity, dosage regimen, the necessity for follow-up, or the interchangeability of booster doses following initial vaccination. Choice of vaccine will ultimately depend on cost and availability.